2022
DOI: 10.3390/molecules28010116
|View full text |Cite
|
Sign up to set email alerts
|

Drug Resistance: The Role of Exosomal miRNA in the Microenvironment of Hematopoietic Tumors

Abstract: Extracellular vesicles (EVs), including exosomes, have an important role thanks to their ability to communicate and exchange information between tumor cells and the tumor microenvironment (TME), and have also been associated with communicating anti-cancer drug resistance (DR). The increase in proliferation of cancer cells alters oxygen levels, which causes hypoxia and results in a release of exosomes by the cancer cells. In this review, the results of studies examining the role of exosomal miRNA in DR, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 195 publications
0
4
0
Order By: Relevance
“…Additionally, research has identified exosomes as an important medium of information exchange through cytoplasmic division, membrane fusion, and receptor-mediated transport, which in turn affect the metabolism and function of recipient cells. 79,80 This action of exosomes links each individual cell together to form a system that synergistically regulates a number of biogenesis…”
Section: Exosome Biogenesis and Applicationsmentioning
confidence: 99%
“…Additionally, research has identified exosomes as an important medium of information exchange through cytoplasmic division, membrane fusion, and receptor-mediated transport, which in turn affect the metabolism and function of recipient cells. 79,80 This action of exosomes links each individual cell together to form a system that synergistically regulates a number of biogenesis…”
Section: Exosome Biogenesis and Applicationsmentioning
confidence: 99%
“…Drug resistance is the main challenge in management in a broad range of cancers, especially in MM. In the process of myelomagenesis, the bone marrow microenvironment provides an intricate network of cellular communication to favor the tumor niche formation [ 147 ]. Targeting this intracellular network provides new opportunities for the therapy of the disease.…”
Section: Potential Therapeutic Strategies Targeting the Exosomes In MMmentioning
confidence: 99%
“…Targeting this intracellular network provides new opportunities for the therapy of the disease. Regarding the importance of exosomal miRNAs in the communications within the BME in developing drug resistance and the progress of the disease, they are considered as desirable therapeutic targets in MM treatment interventions [ 147 ]. Exosome-based strategies in cancer therapy or diagnosis have currently achieved a high level of interest, crucially focusing upon (1) inhibiting exosome-mediated crosstalks by reducing the production of exosomes and/or blocking their uptake, (2) their usage as therapeutic tools for the delivery of drugs, and (3) their role as potential biomarkers for early diagnosis, prognosis, or response to therapy.…”
Section: Potential Therapeutic Strategies Targeting the Exosomes In MMmentioning
confidence: 99%
“…By inhibiting or promoting the transcription and translation of target genes, exosomal miRNAs can affect cell biological functions and play a crucial role in intercellular signaling, cell growth and differentiation, being considered a unique type of regulatory molecules ( Garcia-Martin et al, 2022 ). In the past decade, molecular research has shown that exosomal miRNAs impact the development and progression of an array of diseases, such as metabolic diseases ( Castaño et al, 2018 ; Xu et al, 2022b ), tumors ( Cariello et al, 2022 ), hepatitis ( Qiu et al, 2022 ), renal system diseases ( Zhao et al, 2021a ), cardiovascular diseases ( Du et al, 2021 ), among others, significantly contributing to potential clinical applications.…”
Section: Introductionmentioning
confidence: 99%